FUNCTIONAL FERMENTED MILK DESSERTS BASED ON ACID WHEY - Evdokimov I.A.; Volodin D.N.; Misyura V.A.; Zolotoreva M.S.; Shramko M.I. (Foods and Raw Materials, 2015)
Given the shortage of raw milk, the problem of the rational use of whey as a source of biologically valuable milk components for functional products is urgent. The area of research is the use of acid demineralized whey for the production of functional fermented desserts. Acid whey is characterized by a high content of lactic acid and minerals, which makes its industrial processing difficult and limits the directions of use for food purposes. To solve these problems, the membrane methods area used, they allow regulating the composition and properties of raw materials. Demineralization of acid whey allows removing a significant part of minerals (50%) from it and providing the required acidity in the range, corresponding to raw milk. We set the following objectives: to determine the parameters of whey demineralization, the factors of thermostability; increase stability and improve the consistency of the dairy base from demineralized whey; the effect of the probiotic starter microflora on the characteristics of the final product. In the course of studies, we used a modern membrane equipment, standard and generally accepted research methods. We analysed the composition and properties of demineralized acid whey, considered the theoretical prerequisites to an increase in stability and the ways to improve the consistency of the dairy base. We examined the effect of the dose of stabilizers' salts, dose of the consistency stabilizer and the fat content on physicochemical, organoleptic and rheological parameters of the milk base, as well as the effect of the probiotic cultures ratio in the starter, which make the product functional, on the properties and qualities of the final product. We developed the formulas and technologies of functional desserts. We developed and approved technical specifications for the desserts, based on which the experimental-industrial production is conducted. The feasibility of using demineralized acid whey as a raw material for the production of dessert products is confirmed experimentally.